Analisis Tindak Tutur Pada Spanduk di Tempat Wisata Bukit Kelinci, Sumatera Barat - Silviana Masran; Amelia Yuli Astuti (Jurnal Ilmiah Langue and Parole, 2021)
Banner writing usually uses very direct language and attracts the attention of many people. The research was conducted in the tourist area of ​​Bukit Kelinci, Baso. Data is writing on banners along the Bukit Kelinci tourist area, Baso. The data was taken using the listening method and the free-to-talk technique. In addition, recording and photographing techniques are also used. The data were analyzed using the concept proposed by Searle (1983). The results of the analysis are presented in a descriptive-narrative way. From the analysis of data on the use of language on banners at the Bukit Kelinci tourist spot, Baso, three (3) directive speech acts were found. These three utterances function to invite and prohibit. This is because tourist attractions are usually places to relax with family and friends. In order not to disturb the comfort of the visitors, therefore the visitors are invited to play with the rabbits, as well as to maintain politeness from things that are not desired, the visitors are strictly prohibited not to make out and commit immorality in the area. In the author's opinion, there are still many stories found in tourist attractions in the West Sumatra area, this is because West Sumatra is an area with good and beautiful nature.